Phylogeographical analysis shows the need to protect the wild yaks' last refuge in Nepal. Issue 12 (14th May 2021) - Kusi, Naresh; Manandhar, Prajwol; Senn, Helen; Joshi, Jyoti; Ghazali, Muhammad; Hengaju, Krishna Dev; Suwal, Sanej Prasad; Lama, Tshiring Lhamu; Poudyal, Laxman Prasad; Thapa, Madhuri; Werhahn, Geraldine
Abstract: The wild yak Bos mutus was believed to be regionally extinct in Nepal for decades until our team documented two individuals from Upper Humla, north‐western Nepal, in 2014. The International Union for Conservation of Nature (IUCN) seeks further evidence for the conclusive confirmation of that sighting. We conducted line transects and opportunistic sign surveys in the potential wild yak habitats of Humla, Dolpa, and Mustang districts between 2015 and 2017 and collected genetic samples (present and historic) of wild and domestic yaks Bos grunniens . We also sighted another wild yak in Upper Humla in 2015. Phylogenetic and haplotype network analyses based on mitochondrial D‐loop sequences (~450 bp) revealed that wild yaks in Humla share the haplotype with wild yaks from the north‐western region of the Qinghai‐Tibetan Plateau in China. While hybridization with domestic yaks is a major long‐term threat, illegal hunting for meat and trophy put the very small populations of wild yaks in Nepal at risk. Our study indicates that the unprotected habitat of Upper Humla is the last refuge for wild yaks in Nepal. We recommend wild yak conservation efforts in the country to focus on Upper Humla by (i) assigning a formal status of protected area to the region, (ii) raising awareness in the local communities for wild yak conservation, and (iii) providing support for adaptation of herding practice and pastureland use to ensure the viability of the population. Abstract : Our study carries a global relevance as it presents phylogenetic and haplotype network analyses of wild and domestic yak samples to reveal that the wild yaks in Humla, Nepal, share the haplotype with wild yaks from the north‐western region of the Qinghai‐Tibetan Plateau in China, providing validation to the wild yak rediscovery in Nepal that was based on morphology and behavior of the sighted animals. We also derive phylogeographical inference for the wild yaks in the Nepalese Transhimalayas and discuss their hybridization status while also outlining the conservation implications for the wild yaks that are critically endangered in the country.